THE ILLUSTRATED ENCYCLOPEDIA OF MUSICAL INSTRUMENTS : From all eras and regions of the world - Abrashev, Bozhidar, writer of added text 640703; Gadjev, Vladimir writer of added text 640704 (Cologne : Könemann, 2000)
This illustrated encyclopaedia offers a comprehensive look at the world's musical instruments from the oldest inventions of ancient and primitive societies to the most modern high-tech means of musical expression.